Feasibility study of using natural para rubber for reinforced embankment - Salisa Chaiyaput; Pakkapon Jaroonrat; Anubud Liangsunthonsit; Lindung Zalbuin Mase; Pornsuda Kotkhangphlu; Jiratchaya Ayawanna (My University, 2023)
This research developed a natural para rubber from rubber tree sap as a biodegradable-reinforced material in geogrid application with the purpose of membrane support, bearing capacity increment, and lateral restraint in embankment construction. Biaxial geogrids with an aperture size of 20 mm × 20 mm were prepared from the ribbed smoked sheet (RSS) made of the coagulated latex sheets, and rubber compound sheet (RCS) made of chemically modified RSS sheet to increase the rubber performance were investigated and compared. The performance of RSS and RCS was evaluated under the actual situation in a field test with an area of 4.5 m-length x 1 m-width with 0.5 m-depth. In each studied area of the reinforced zone, RSS and RCS were separately inserted at 250 and 450 mm from the base of a field test as the 1st and 2nd reinforcement layers, respectively. The load was applied to simulate the traffic load. The RSS- and RCS-reinforced zones in the field test were compared with the non-reinforced zone in terms of settlement and rut depth. The drastic settlement and rut depth were significantly detected in non-reinforced zones compared to the reinforced zones. Meanwhile, higher settlement and rut depth were observed at RSS-reinforced zones compared to the RCS-reinforced zones. The RCS geogrid in this research was successfully applied as a functional biodegradable-reinforced material for embankment construction.
Keywords: Geogrid; Settlement (finance); Crumb rubber; RSS; Geotechnical Engineering and Soil Stabilization